Laser cooling of ytterbium-doped silica glass by more than 6 Kelvin - Peysokhan, Mostafa; Rostami, Saeid; Mobini, Esmaeil; Albrecht, Alexander R.; Kuhn, Stefan; Hein, Sigrun; Hupel, Christian; Nold, Johannes; Haarlammert, Nicoletta; Schreiber, Thomas; Eberhardt, Ramona; Flores, Angel S.; et al. (2021 Conference on Lasers and Electro-Optics, CLEO 2021 - Proceedings, 2021)
We report nearly an order of magnitude improvement over the lowest temperature achieved in laser-cooling of Yb-doped silica glass. The 6K cooling relative to the ambient temperature was achieved by pumping the sample at 1035nm.
CRIS-Team Scopus Importer:2023-04-20